Low-Cost, Open-Source, and Low-Power: But What to Do With the Data? - Horsburgh, Jeffery S.; Caraballo, Juan; Ramírez, Maurier; Aufdenkampe, Anthony K.; Arscott, David B.; Damiano, Sara Geleskie (Frontiers in Earth Science, 2019)
There are now many ongoing efforts to develop low-cost, open-source, low-power sensors and datalogging solutions for environmental monitoring applications. Many of these have advanced to the point that high quality scientific measurements can be made using relatively inexpensive and increasingly off-the-shelf components. With the development of these innovative systems, however, comes the ability to generate large volumes of high-frequency monitoring data and the challenge of how to log, transmit, store, and share the resulting data. This paper describes a new web application that was designed to enable citizen scientists to stream sensor data from a network of Arduino-based dataloggers to a web-based Data Sharing Portal. This system enables registration of new sensor nodes through a Data Sharing Portal website. Once registered, any Internet connected data-logging device (e.g., connected via cellular or Wi-Fi) can then post data to the portal through a web service application programming interface (API). Data are stored in a back-end data store that implements Version 2 of the Observations Data Model (ODM2). Live data can then be viewed using multiple visualization tools, downloaded from the Data Sharing Portal in a simple text format, or accessed via WaterOneFlow web services for machine-to-machine data exchange. This system was built to support an emerging network of open-source, wireless water quality monitoring stations developed and deployed by the EnviroDIY community for do-it-yourself environmental science and monitoring, initially within the Delaware River Watershed. However, the architecture and components of the ODM2 Data Sharing Portal are generic, open-source, and could be deployed for use with any Internet connected device capable of making measurements and formulating an HTTP POST request.